2005
DOI: 10.1007/s00244-004-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium(II), Chromium(VI), and Arsenic(V) on Long-Term Viability- and Growth-Inhibition Assays Using Vibrio fischeri Marine Bacteria

Abstract: As a complement to previous results obtained using the standard Microtox acute-toxicity test, which is based on measuring the rapid decrease of bioluminescence (5 to 30 minutes of exposure) in Vibrio fischeri bacteria in the presence of toxicants, the long-term effects of Cd(II), Cr(VI), and As(V) were studied on growth rate and viability assays of the same bacteria adapted to longer-lasting cultures, i.e., 48 or 72 hours instead of 5 or 30 minutes. Effects on viability or growth, as studied by establishing do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 28 publications
5
25
1
4
Order By: Relevance
“…In the Microtox ® assay, antagonism dominated the toxicity of heavy metal mixtures, while synergism was obtained for the binary mixtures of pesticides (Table 5). Our results agreed with those reported by Fulladosa et al (2005) regarding to the antagonistic effect of Cd-Pb and Cu-Pb mixtures against Vibrio fischeri bacteria.…”
Section: Journal Of Biology and Life Sciencesupporting
confidence: 93%
See 2 more Smart Citations
“…In the Microtox ® assay, antagonism dominated the toxicity of heavy metal mixtures, while synergism was obtained for the binary mixtures of pesticides (Table 5). Our results agreed with those reported by Fulladosa et al (2005) regarding to the antagonistic effect of Cd-Pb and Cu-Pb mixtures against Vibrio fischeri bacteria.…”
Section: Journal Of Biology and Life Sciencesupporting
confidence: 93%
“…ISSN 2157-6076 2015 Cd and Pb reported by different investigators, compared with our results. It seems that our result for Cd (4.47 mg/L) was very low as compared with those reported by Codina et al (1993), Newman and McCloskey (1996), Mowat and Bundy (2002) and Fulladosa et al (2005); which respectively equaled to 34.70, 21.90, 59.30 and 10.90 mg/L. For Cu and Pb, the opposite was obtained where our EC50 values (2.84 and 5.83 mg/L, respectively) were generally higher than those reported by other investigators (Table 6).…”
Section: Journal Of Biology and Life Sciencecontrasting
confidence: 85%
See 1 more Smart Citation
“…A clear hormesis phenomenon caused by the presence of Cd(II) in low concentrations, under the conditions of both viability and growth-inhibition assays with V. fischeri has been already reported [37].…”
Section: Sensitivity Of Bacterial Tests -Comparison To D Magnamentioning
confidence: 71%
“…In a study of the effects of As(III) and As(V) on V. fischeri, chemical speciation was found to be correlated with toxicity [13]; this could explain why it was difficult to obtain a clear EC50. In the same study, a correlation was observed between toxicity and pH; i.e., changes in pH of the pollutant solutions resulted in improvement or reduction of the EC50.…”
Section: Discussionmentioning
confidence: 98%